The Influence of Social Sciences Teachers in Overcoming Forgetting and Learning Boredom on Students' Learning Achievement in Grade X of SMA Negeri 1 Panyabungan Utara - Husein NST, Ahmad; Ansari, Rajab (International Journal of Educational Research Excellence (IJERE), 2025)
The formulation of the research problem is "Is There an Effect of Social Studies Teachers in Overcoming Forgottenness and Study Boredom on Student Achievement in Class X IPS at SMA Negeri 1 Panyabungan Utara in the Academic Year 2024-2025." The research objective was to determine the effect of social studies teachers in overcoming forgetfulness and learning saturation on students' learning achievement. Population and Sample using cluster random sampling technique. Type of quantitative research. Data collection using questionnaires and tests. The formula used is the formula "multiple product moment correlation". Based on the results of the research that the author conducted through the product moment correlation formula, the results obtained r count = 0.705 by looking at the r table list with a sample size of 21 with a 5% error interval level is 0.433. In accordance with the provisions if rcount > rtable then the alternative hypothesis Ha can be accepted, conversely if rcount < rtable then Ha is rejected. From this provision, it is obtained 0.705 > 0.433, so it is said that the truth is accepted. This shows that there is an influence of social studies teachers in overcoming forgetfulness and boredom of learning on student achievement in class X IPS at SMA Negeri 1 Panyabungan Utara for the 2024-2025 academic year.